Divergent synthesis of cyclic ketones via a ring-closing metathesis and oxidation method - Jorge Cruz-Huerta; Ericka Santacruz; Alejandro Castro; Jorge García-Dávila; Amado Grandes-Blanco (Results in Chemistry)
Allylation of aldehydes was employed in combination with ring-closing metathesis (RCM) and oxidation reactions to achieve the synthesis of cyclic conjugated ketones. The synthetic strategy involved RCM of the mutual homoallylic alcohol intermediate followed by oxidation reaction to afford the six-membered cyclic enone. Moreover, when oxidation and RCM were completed successively, the five-membered cyclic enone was obtained.